Ekonomi Maritim Kesultanan Makasar Abad XVII M - M. Nur Ichsan Azis (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2013)
Nusantara maritime trade has developed rapidly in the mid-sixteenth century to the end of the seventeenth century AD Influx of traders from Asia and Europe made a crowded archipelago. The main objective is to find the traders of spices that are in the Moluccas. To reach the Moluccas, the traders have to pass the island of Sulawesi. This area, Sulawesi, was a local liaison between producing spices and traders who need it. This condition can be well used by the Sultanate of Makassar on the island of Sulawesi. With the opening of transit ports and airports of international trade, Makassar can reach its peak that relies on maritime trade in XIIV century AD.